The 5-year experience in short-term circulatory support in post myocardial infarction patients: a report from INCORMACS registry - Pitta Acevedo, Manuel (2020)
Objective. To determine the clinical and epidemiological characteristics of patients with short-term mechanical circulatory support devices (MCSD) after myocardial infarction (MI) at a national referral hospital. Materials and methods. Descriptive, retrospective study of post-MI patients in whom short-term mechanical circulatory support devices were implanted from 2015 to 2020. Results. Nine mechanical support devices were implanted, in the same number of patients due to cardiogenic shock post MI. All patients were men with ST-elevation myocardial infarction (STEMI). Eight extracorporeal membrane oxygenation devices (ECMO) and one centrifugal flow pump (in LVAD configuration) were implanted. The median time of use of the devices was eight days. The most frequent complications were non-fatal bleeding (55.6%), acute kidney injury (44.4%) and sepsis (44.4%).In-hospital mortality was 55.6 %. Conclusions. The use of short term MCSD after myocardial infarction is still limited in our institution and its main representative is the ECMO post STEMI complicated by cardiogenic shock. Despite the use of these devices, in-hospital mortality is high.